PENGARUH ELECTRONIC WORD OF MOUTH (EWOM) PADA ONLINE TRAVEL AGENT (OTA) TRAVELOKA TERHADAP KEPUTUSAN MENGINAP DI TOPAS GALERIA HOTEL, BANDUNG - Senny Handayani Suarsa (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
The results of this study are expected to be used by Topas Galeria Hotel to assess Electronic Word of Mouth (eWOM) on Traveloka's Online Travel Agent (OTA) influences the decision to stay. Besides, the relationship between E-WOM activities in OTA can be used as a reference for Topas Galeria Hotel to determine the desires and expectations of prospective consumers in the future. Data were collected by a self-administered survey involving 384 respondents who made reservations at Topas Galeria Hotel through OTA Traveloka. The results showed that all indicators had a positive and significant influence on the decision to stay at Topas Galeria Hotel. Thus the hypothesis is proven, and the most influential dimension is the Valence of Opinion Dimension.